Matrix Transforms of Summability Domains of Zweier Method - Ants Aasma (Journal of Advances in Applied & Computational Mathematics, 2018)
Let Z1/2 be the Zweier method, and B and M matrices with real or complex entries. In the present paper, we find necessary and sufficient conditions for M to be transform from the summability domain of Z1/2 into the summability domain of B if B is lower triangular. For an infinite matrix B, we consider only sufficient conditions.